An investigation into the linguistic features of performatives in speeches in cultural events in English and Vietnamese - Bui, Thi Khanh Yen.; Ngũ, Thiện Hùng, Ph.D. (Đà Nẵng : The University of Da Nang, 2012)
Introduction; Literature review and theoretical background; Methods and procedures...
Master thesis in the English language. Field: The English language. Code: 60.22.15.
Keywords: English language; English language -- Linguistic; English language -- Speeches